Nilai kerugian masyarakat akibat banjir di Kecamatan Pujud Kabupaten Rokan Hilir - Rita Novita; Hainim Kadir; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to identify the social and economic characteristics of the respondents in Pujud Rokan Hilir and calculate the value of the loss given/to society due to floods. This study used a random cluster sampling technique then selected 44 samples. The data used in this study is primary data and secondary data. method of analysis used in this study is descriptive and qualitative methods. The result showed that the socioeconomic characteristics of the respondents were dominated by the male gender with low levels of education, namely graduate elementary school (SD), while the majority of this type of work is the income of farmers by respondents at the level Rp.431.250,00 - Rp.3.026.040 , 00 and the number of dependents 4-6 people with 42-51 years old stay and residence status is dominated by natives. Communities received a total loss when a flood is Rp.21.905.140.464,-.Keywords: Flood, the value of loss, loss of income, medical expenses and repair costs